Efectos de la aplicación de ceniza de madera en la morfología y rendimiento del cultivo de fréjol (Phaseolus vulgaris L.) en la parroquia Patricia Pilar del Cantón Buena Fe. - Heredia Delgado, Jamil Benjamín (2020)
The use of new alternatives that allow improving the nutritional status and pH of the soil and increasing its productive potential is one of the expectations of this research when using vegetable ash in the cultivation of beans. For this reason, the present investigation aimed to evaluate the effects of the application of wood ash in the cultivation of beans (Phaseolus vulgaris L.) variety EVG-6. The test was carried out at the Teresita 2 farm, located at km 51 via Quevedo - Santo Domingo. The experiment was carried out under a randomized complete block design (DBCA) with 5 treatments in 4 repetitions. The evaluated treatments were T1: 500 kg ha-1 of wood ash, T2: 750 kg ha-1 of wood ash, T3: 1000 kg ha-1 of wood ash, T4: 1250 kg ha-1 of wood ash and T5: Control without application. The results obtained showed that the application of the different doses of wood ash did not influence the number of days to flowering, as well as the weight of 100 grains, showing averages of 34 days and 33.83 g, respectively. When the wood ash was applied in doses of 1250 kg ha-1, a greater growth of the plants was observed (61.73 cm in height), as well as a higher production of pods per plant (23 pods), more grains per pod (7 grains), generating a higher yield that amounted to 1259-79 kg ha-1. In addition to generating higher yields, when 1250 kg ha-1 of wood ash was applied, a higher profitability was also obtained that amounted to 50.54%. Keywords: integral use, fertilization, combustion